(3EfHGA GrdZeQ HCHfGA GrdoYeQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s ((3YeQ Hf YHO Gddg GdeWQGhi s)
(3ChdgG (B:s
(3gPG JYdjb LeYJ ajg MhGOK GdReGf GdPi COQcJg efP ehdOi SfI (B773(3g` hgd LQG , eaUdkG ai cd SfI Yf hajGJ GdGYjGf s
(3BNQgG (B:s
(3ajg LeGd GdOjf GdfGUQ aCPf HbJdg abJd hcGfJ dg eYQaI hgeI YGdjI BNQ GdeLdO GdChd s
(3fSNI NGeSI GdLRA GdChd ef fSNI CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B32 s
(3eUOQ GbJfGA GdCUd (B:s
(3eOjfg (B(522) s
Keywords: (3GdJGQjNs